Implikasi Hukum Penggusuran Paksa di Kota Dili terhadap Hak Asasi Warga Negara - Carolina da Cruz; Francisco Ruas Hornay (Jurnal Interpretasi Hukum, 2026)
The purpose of this study is to determine and explain the legal implications of forced evictions in the city of Dili on the human rights of citizens and to determine and explain the state's responsibility in protecting citizens' housing rights from the practice of forced evictions in the city of Dili. The approach method uses a normative juridical approach to law, which is carried out by examining written norms, thus forming secondary data, sourced from primary, secondary, and tertiary legal materials. The data obtained is then analyzed using a qualitative analysis approach. Based on the results of the conclusion that the legal implications of forced evictions in Dili City on the human rights of citizens are a violation of international law and the national law of Timor Leste, which has the potential to cause social instability, poverty and vulnerability, especially for vulnerable groups. Forced evictions in areas such as Tasi Tolu in Timor-Leste violate human rights, including the right to adequate housing, the right to a decent standard of living, and the right to security. The State's Responsibility in Protecting Citizens' Housing Rights from Forced Eviction Practices in Dili City to protect the right to housing from forced evictions in Dili is realized through the constitution and laws they have made. The government has an obligation to respect, protect, and fulfill human rights, including the right to adequate housing, and to prevent discrimination in policy. This is affirmed in the constitution and supported by the enactment of the Land Law, which aims to clarify land ownership status and provide a mechanism for dispute resolution.